Expectation-maximization-based channel estimation algorithm for OFDM visible light communication systems - Soubhi Hussein, Yaseein; Yusoff Alias, Mohamad; A. Abdulkafi, Ayad; Omar, Nazaruddin; Kamarulzamin Bin Salleh, Mohd (International Journal of Engineering and Technology, 2018)
The tremendous growth of indoor communication requires increased capacity and appropriate quality of services. Visible light communica-tion (VLC) is a green technology that shows great promise in terms of its ability to meet the demand for communication services. Orthogo-nal frequency division multiplexing (OFDM) enables VLC to provide a higher data rate and to combat inter-symbol interference. However, an accurate and efficient channel estimation method is needed for coherent demodulation at the receiver end of an OFDM system. In this paper, a new algorithm for OFDM-based VLC systems is proposed. The algorithm is based on expectation maximization and is called the expectation maximization for visible light communication (EM-VLC) algorithm. The algorithm is implemented to find the maximum-likelihood (ML) estimation of the channel impulse response and to find unknown parameters. In addition, a low-rank minimum mean square error (lr-MMSE) estimator algorithm is developed and its performance is compared with least squares (LS) and minimum mean square error (MMSE) estimators. The proposed EM-VLC algorithm improves the performance of OFDM VLC systems by significantly reducing the bit error rate (BER) and consequently increasing system throughput. The simulation results demonstrate that the EM-VLC algorithm outper-forms the three channel estimation algorithms, LS, MMSE and lr-MMSE.Â Â